Fatores associados à capacidade antioxidante total da dieta de gestantes brasileiras - CARVALHO, Roberta Rejane Santos de (2023)
Introduction: Pregnancy is considered a phase of oxidative stress, in which the demands for nutrients with antioxidant properties are increased. The total antioxidant capacity of the diet (TACd) is an instrument that evaluates the consumption of antioxidants present in the diet. Objective: The present study aimed to analyze the association of socioeconomic, regional, trimester and nutritional status factors with the CATd of Brazilian pregnant women participating in the “Multicentric Study on Iodine Deficiency (EMDI-BRASIL)”, carried out in eleven centers and distributed in nine states and the Federal District. Methods: This is a cross- sectional study with 2232 pregnant women, aged 18 years or older, in the first, second or third trimester of pregnancy, assisted by teams from Basic Health Units in eleven cities in Brazil, namely Aracaju, Belo Horizonte, Brasília, Macaé, Palmas, Pinhais, Ribeirão Preto, Rondonópolis, São Luís, Viçosa and Vitória, who reported not having thyroid disease (hypothyroidism, hyperthyroidism, Hashimoto's disease and neoplasms) or surgery on the thyroid gland. A semi-structured questionnaire was used to assess socioeconomic, demographic and health data and a 24-hour recall (R24h) was used to assess dietary intake. The total antioxidant capacity of the diet was obtained through the consumption of foods and beverages reported in the R24h and with the aid of tables that used the “ferric reducing-antioxidant power” (FRAP) method to calculate the amount of antioxidants in each food. Associations between sociodemographic factors and total dietary antioxidant capacity were analyzed using logistic regression. Results: The median CATd of pregnant women was 5.32 mmol/day. Pregnant women aged 20 to 34 years (OR:1.86; CI 95%; 1.26-2.76), 35 years or older (OR:3.68; CI 95%; 2.21-6.14) and who were in the second trimester of pregnancy (OR:1.50; CI 95%; 1.11-2.01) were more likely to be in the highest CATd tertile. While pregnant women with higher education (OR: 0.67; CI 95%; 0.48-0.92) were 67% less likely to be in the highest CATd tertile. Conclusion: The present study demonstrated that there are differences in the consumption of antioxidants in different cities in Brazil and that associated factors such as age, education and the gestational trimester can impact the intake of foods rich in antioxidants. We encourage the creation of public policies focused on these more vulnerable groups and alert health professionals about the need to reinforce the importance of a diet rich in antioxidants during prenatal care.